2018
DOI: 10.4103/jfmpc.jfmpc_345_16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nasal colonization of methicillin-resistant Staphylococcus aureus among schoolchildren of Barabanki district, Uttar Pradesh, India

Abstract: Introduction:The study aimed to determine the prevalence of nasal colonization of methicillin-resistant Staphylococcus aureus (MRSA), the minimum inhibitory concentration (MIC) of oxacillin and vancomycin, inducible clindamycin resistance, and antimicrobial resistance pattern of S. aureus among children of Barabanki district, Uttar Pradesh, India.Materials and Methods:School-going children of age group of 5–15 years were identified and selected according to the inclusion and exclusion criteria. Two nasal swabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…Our nding was also similar to those reported from other countries [18][19][20] . However, the nasal carriage rate of S. aureus in this study tends to be lower than that reported in Nigeria (56.3%), India (46.67%), United State of America (39.6%; age group 1-19 years old), Netherland (36%; age group 1-19 years, and Nepal (31%; age group less than 15 years old) [21][22][23][24][25] . On the other hand, the prevalence of S. aureus among school children in our study was higher than that reported in China (5.1%), Serbia (2.59%), and Iraq (17.75%) [26][27][28] .…”
Section: Discussioncontrasting
confidence: 68%
“…Our nding was also similar to those reported from other countries [18][19][20] . However, the nasal carriage rate of S. aureus in this study tends to be lower than that reported in Nigeria (56.3%), India (46.67%), United State of America (39.6%; age group 1-19 years old), Netherland (36%; age group 1-19 years, and Nepal (31%; age group less than 15 years old) [21][22][23][24][25] . On the other hand, the prevalence of S. aureus among school children in our study was higher than that reported in China (5.1%), Serbia (2.59%), and Iraq (17.75%) [26][27][28] .…”
Section: Discussioncontrasting
confidence: 68%
“…Rates of nasal carriage of MRSA have been studied by various investigators in India, and they range from 7.7% in school children, 3%–10% in predominantly outpatient population to 7.5%–25% in health care workers, highlighting the potential role of health care workers in the transmission 2629. However, the present study lacks MRSA carrier status estimation, molecular characterization, and panton-valentine leukocidin toxin carriage status.…”
Section: Discussionmentioning
confidence: 86%
“…All of the 40 studies were considered for qualitative as well as the quantitative synthesis of etiological agents. Ultimately, only 34 of 40 studies were included in the MRSA meta-analysis, 8,9,15 -46 as the remaining 6 studies did not include data relevant to MRSA (4 efficacy studies, 1 study that described heteroresistance to vancomycin among methicillin-resistant S. aureus isolates, and 1 survey wherein no exact data on prevalence were presented). 47 -52 Table 1 represents the characteristics of the studies included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…8,[11][12][13] Furthermore, few studies from the country suggest an impact of age and gender on MRSA carriage. 14,15 It is imperative to understand the prevalence of risk factors, such as age and gender, on MRSA colonization at the country level to facilitate the implementation of appropriate infection control measures. This systematic review and meta-analysis was conducted to assess the prevalence, burden and epidemiology of methicillin-resistant S. aureus (MRSA).…”
Section: Introductionmentioning
confidence: 99%